First principles insights into triboelectrification during solid-solid contact: The curious case of 2D MXenes and aluminum - Abbas, Ghulam; Alay-e-Abbas, Syed Muhammad; Larsson, J. Andreas; Shi, Yijun (Nano energy, 2024)
Recently, triboelectric nanogenerators (TENGs) have been widely used for energy harvesting and self-powered sensing due to their significant and unique advantages. However, the intrinsic mechanisms that contribute to tribo-electricification (TE) between two materials remain as a subject of rigorous debate. In addition to predicting the qualitative charge transfer in solid-solid contacts based on the difference in the work functions of the two moieties constituting the interface, we argue that it is essential to obtain atomic-level, first principles, insights into the bonding properties, quantitative charge transfer, and the possible presence of a electrostatic potential barrier at the interface to fully understand the TE mechanism of a system. We have utilized dispersion-corrected density functional theory (DFT) calculations in this study to systematically investigate the TE potential of bare surface Ti3C2 and Ti3N2 2D MXene monolayers and their surface functionalized modifications Ti3C2R2 and Ti3N2R2 (where R = -O, -OH, or -F) in contact with Al(111). For these heterostructures, we have analyzed the adhesive energy of the interfaces, the nature of interaction through the electron localization function (ELF), and the charge distribution, which have revealed distinct characteristics of MXene/Al contacts for these monolayer/metal interfaces at their equilibrium distance and the changes in their properties under uniaxial pressure. Among all the metallic 2D MXene variants investigated in this study, we have determined that Ti3C2F2/Al and Ti3N2F2/Al interfaces show exceptional potential for TE. [Display omitted] •A first-principles study on the mechanism of MXene-Al contact electrification is performed.•MXenes with different surface functionalizations are assessed for their role in the contact electrification process.•Crucial insights into different types of interface contacts and their potential in contact electrification are revealed.•A comprehensive assessment of interface barrier variations and their role in the dynamics of contact electrification is performed.